Yang Jiang. Six Chapters from My Life "Downunder". Traducido por Howard Goldblat y con un prefacio de Jonathan Spence. Seattle y Londres, University of Washington Press, 1984. - Botton Beja, Flora (El Colegio de México, 1985)
-